3D MOF Nanoarchitecture Membrane via Ultrafast Laser Nanoforging. Issue 11 (3rd October 2021) - Liu, Xingtao; An, Licong; Xiang, Sen; Jiang, Haoqing; Cheng, Gary J.
Abstract: Metal‐organic framework (MOF) crystals are useful in a vast area of applications because of their unique chemical and physical properties. Manufacturing of an integrated MOF membrane with 3D nanoarchitectures on the surface is especially important for their applications. However, as MOF crystals usually exist as powdery crystals, fabrication of their large area, monolithic, and high‐resolution patterns is challenging. Here, it is found that isolated MOF nanocrystals could be directly converted to a monolithic MOF film with designed 3D nanoarchitectures/patterns via an ultrafast laser induced nanoforging without binders. During the nanosecond laser shock, the voids among MOF nanocrystals are eliminated due to the surface amorphization effect, which allows the fusing of the MOF nanocrystals on the grain boundaries, leading to the formation of a dense film while preserving the nature of the pristine MOF. The high strain rate by laser enhances formability of MOFs and overcomes their brittleness to generate arbitrary 3D nanoarchitectures with feature sizes down to 100 nm and high productivity up to 80 cm 2 min –1 . These 3D MOF nanoarchitectures also exhibit boosted mechanical strength up to 100% compared with their powdery particles. This method is facile and low‐cost and could potentially be used in various fields, such as devices, separation, and biochemical applications. Abstract : A straightforward method is proposed for the direct conversion of MOF powder to monolithic 3D nanoarchitectures with high resolution and strength. This is achieved by laser induced nanoforging of MOF nanocrystals under extremely high strain rates. The surficial amorphization of MOF under high pressure links the crystals together while maintaining the high porosity and crystallinity on average.